2017
DOI: 10.1016/j.ygyno.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Three versus six cycles of adjuvant platinum-based chemotherapy in early stage clear cell ovarian carcinoma – A multi-institutional cohort

Abstract: Objectives To determine if 6 versus 3 cycles of adjuvant platinum-based chemotherapy with or without taxane impacts survival in early stage ovarian clear cell carcinoma (OCCC). Methods We retrospectively identified all cases of stage I and II OCCC treated at 5 institutions from January 1994 through December 2011. Patients were divided into 2 groups: those who received 3 versus 6 cycles of adjuvant chemotherapy. Our cohort consisted of 210 patients with stage IA-II disease, 116 of whom underwent full surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…[12] An exploratory analysis broken down by histology suggested that patients with HGSC histology benefit from 6 cycles of chemotherapy but OCCC histology does not. [13] A recent retrospective cohort confirmed this finding, [14] raising the question of the efficacy and optimal number of cycles of upfront chemotherapy for OCCC.…”
Section: Introductionmentioning
confidence: 81%
“…[12] An exploratory analysis broken down by histology suggested that patients with HGSC histology benefit from 6 cycles of chemotherapy but OCCC histology does not. [13] A recent retrospective cohort confirmed this finding, [14] raising the question of the efficacy and optimal number of cycles of upfront chemotherapy for OCCC.…”
Section: Introductionmentioning
confidence: 81%
“…With regard to the number of chemotherapy cycles, Prendergast et al reported that analyzing 38 (18.1%) patients received 3 cycles, and 172 (81.9%) patients received 6 cycles of mainly carboplatin-paclitaxel chemotherapy, and recurrence was comparable between the groups (18.4 vs. 27.3% for 3 vs. 6 cycles, respectively, N.S.). There was no impact of 3 versus 6 cycles of chemotherapy on recurrence-free or overall survival on univariate analysis ( NS ) [ 9 ]. These observations demonstrated that the effect of postoperative chemotherapy in CCC patients is so limited that the control of the budding of “recurrence seeds” and subsequent proliferation is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…94 A study of 210 patients showed that there was no impact of three versus six cycles of chemotherapy on overall survival in earlystage clear cell carcinoma. 95 Further studies of early-stage disease are required to determine which stages of disease benefit from chemotherapy and how many cycles of adjuvant chemotherapy are appropriate. At present, the Japanese Gynecologic Oncology Group (JGOG) is performing a randomized phase III trial to evaluate the necessity of adjuvant chemotherapy in stage I epithelial ovarian cancer (stage IA/IB clear cell carcinoma or grade 2/3 other histological type and stage IC1 with all grades and histological types) after comprehensive staging surgery (JGOG3020, UMIN000008481).…”
Section: Surgerymentioning
confidence: 99%